84.2k views
0 votes
Factor completely: 8x5 + 28x4 + 12x3

1 Answer

2 votes

Answer: The answer is
4x^3(x+3)(2x+1).


Step-by-step explanation: Given expression is


8x^5+28x^4+12x^3.

To factorise the given expression, first we need to take common the powers of 'x' which are common to all the three terms. Then, we need to factorise the remaining expression using the formula


x^2+(a+b)x+ab=(x+a)(x+b).

Let us start as follows


8x^5+28x^4+12x^3\\\\=4x^3(2x^3+7x+3)\\\\=4x^3(2x^3+6x+x+3)\\\\=4x^3\{2x(x+3)+1(x+3)\}\\\\=4x^3(x+3)(2x+1).

Thus, the required factorised expression is


4x^3(x+3)(2x+1).



User WebQube
by
6.0k points